2004
DOI: 10.1111/j.1467-8489.2004.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the economic inefficiency of Nepalese rice farms using data envelopment analysis

Abstract: A data envelopment analysis of a sample of 76 Nepalese rice farmers reveals average relative economic, allocative, technical, pure technical and scale inefficiencies as 34, 13, 24, 18 and 7 per cent, respectively. The significant variations in the level of inefficiency across sample farms are attributed to the variations in the 'use intensities' of resources such as seed, labour, fertilisers and mechanical power. In addition, a second stage Tobit regression shows the variation is also related to farm-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
91
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 69 publications
15
91
3
5
Order By: Relevance
“…The positive effect of producer age on technical inefficiency suggests that younger farmers are more likely to be technically efficient than their older counterparts. This is consistent with the findings of Dhungana et al (2004) who showed that, in Nepalese rice farms, younger farmers may be more willing to adopt new technologies and/or to have a stronger educational background. The households that had a higher number of family members performed better in terms of technical efficiency.…”
Section: Truncated Bootstrap Analysis Of Sources Of Inefficiencysupporting
confidence: 81%
See 1 more Smart Citation
“…The positive effect of producer age on technical inefficiency suggests that younger farmers are more likely to be technically efficient than their older counterparts. This is consistent with the findings of Dhungana et al (2004) who showed that, in Nepalese rice farms, younger farmers may be more willing to adopt new technologies and/or to have a stronger educational background. The households that had a higher number of family members performed better in terms of technical efficiency.…”
Section: Truncated Bootstrap Analysis Of Sources Of Inefficiencysupporting
confidence: 81%
“…Furthermore, the results indicate that formal education and additional years of management experience resulted in lower technical inefficiency. This implies that increasing investment in formal and informal education might lead to better performance in the agricultural sector (Dhungana et al 2004) and that education and experience are substitutes and play a significant role in the level of technical inefficiency. The positive effect of producer age on technical inefficiency suggests that younger farmers are more likely to be technically efficient than their older counterparts.…”
Section: Truncated Bootstrap Analysis Of Sources Of Inefficiencymentioning
confidence: 99%
“…A possible explanation of the positive coefficienct of experiece could be that the farmers have more valuable experience by hands-on learning and tends to affect use of inputs efficienctly. The results of this study are consistent with the findings of the study conducted by [6,20,[23][24][25][26].…”
Section: Resultssupporting
confidence: 83%
“…Such variables are termed as two-sided censored variables. The most frequently used method to predict the values of such variables is the two-limit tobit regression model [17,28,[44][45][46]. In our case, the dependent variable represents a proportion, which requires that there should not be an excessive amount of censoring (values of zero and one).…”
Section: Determinants Of Allocative Efficiency-two-limit Tobit Regresmentioning
confidence: 99%